Biochemical changes in the larval stages of an edible estuarine crab Thalamita crenata (Latreille) fed with different diets - Kannupandi, T; Murugadasu, P; Soundarapandian, P; Shanmugam, A (Indian Journal of Fisheries, 2011)
When the larvae were fed with Coscinodiscus sp. and Ariemia naupHi diets, thedevelopment was complete and the protein content increased from first zoeal stageto fifth zoeal stage and decreased in megalopa stage. Lipid content showed a steadyincrease in all the stages; but the carbohydrates content showed an increase uptothird zoeal stage then a decrease in the fourth and fifth zoeal stages and againan increase in the megalopa stage. In general, when the larvae were fed withThalassiothrix longissima, Nitzschia sp. and Skeletonema sp., more carbohydrateaccumulated. But when the larvae were fed with Artemia nauplii and Coscinodiscussp., protein and lipid increased during the larval development.